The Economic Condition of the Bishopric of Gaza (Palestine) during the Rule of Bishop Porphyry (circa 395–420) - Milewski, Ireneusz (Studia Ceranea, 2018)
The study attempts to determine the economic condition of a small provincial bishopric, namely the church of Gaza (Palestine) during the rule of bishop Porphyry (circa 395–420 AD). All of the information on the subject comes from the Vita Porphyrii by Mark the Deacon – a source whose historical value has often been disputed. Although the information on the wealth of the church in Gaza at the turn of the 4th and 5th centuries is not particularly vast or illuminating, it is nevertheless possible to identify several spheres of economic activity of the Gaza bishopric. These are, among other things, the property owned by the bishopric (real estate), its cash reserves (mostly at the beginning of the 5th century), the endowments of the imperial court (given by emperor Arcadius and his wife, empress Aelia Eudoxia), as well as the charitable activity of the bishopric (especially on the occasion of erecting the Eudoxiane, probably in 407).